Insight into Classification and Risk Stratification of Head and Neck Squamous Cell Carcinoma in Era of Emerging Biomarkers with Focus on Histopathologic Parameters - Mäkitie Antti A.; Agaimy Abbas; Almangush Alhadi (MDPI, 2023)
Tumor-node-metastasis (TNM) staging system is the cornerstone for treatment planning
of head and neck squamous cell carcinoma (HNSCC). Many prognostic biomarkers have been
introduced as modifiers to further improve the TNM classification of HNSCC. Here, we provide an
overview on the use of the recent prognostic biomarkers, with a focus on histopathologic parameters,
in improving the risk stratification of HNSCC and their application in the next generation of HNSCC
staging systems.